Age-related treatment patterns for stage I NSCLC in three European countries. Issue 8 (November 2021) - Damhuis, Ronald A.M.; Senan, Suresh; Khakwani, Aamir; Harden, Susan; Helland, Ȧslaug; Strand, Trond-Eirik
Abstract: Introduction: Surgery is the preferred treatment for patients with early-stage non-small cell lung cancer (NSCLC) while stereotactic body radiation therapy (SBRT) may be applied in patients with major comorbidity or high age. We evaluated the association between age and treatment utilization for early-stage NSCLC in patients diagnosed in 2015–2016 in three European countries. Patients and methods: Information was retrieved from population-based registries in England, Norway and the Netherlands. Treatment patterns and two-year overall survival rates for 105, 124 patients with clinical stage I were analysed by age-group. Results: Surgical resection rates were higher in Norway (55%) and England (53%) than in the Netherlands (47%), and decreased with increasing age. SBRT use was highest in the Netherlands (41%), followed by Norway (29%) and England (12%). In the Netherlands, SBRT was the prevailing treatment in patients aged 70 years or older. In octogenarians, the proportion not receiving curative intent treatment was 53% in England, versus 35% in Norway and 22% in the Netherlands. Two-year survival rates were better for surgery than for SBRT and slightly better in Norway. Conclusion: In patients aged 70 years or older, the proportion not receiving any curative treatment remains substantial, and differs significantly between countries. Measures to address these disparities are needed.